New Insight of Circular RNAs' Roles in Central Nervous System Post-Traumatic Injury - Xu, Lvwan; Ye, Xin; Zhong, Jinjie; Chen, Ying-ying; Wang, Lin-lin (Frontiers in Neuroscience, 2021)
The central nervous system (CNS) post-traumatic injury can cause severe nerve damage with devastating consequences. However, the pathophysiological mechanisms of it remain vague. There is still an urgent need for more effective treatments. Circular RNAs (circRNAs) are noncoding RNAs that can form covalently closed RNA circles. Through second-generation sequencing technology, microarray analysis, bioinformatics, and other technologies, recent studies have shown that a number of circRNAs are differentially expressed after traumatic brain injury (TBI) or spinal cord injury(SCI). These circRNAs play important roles in proliferation, inflammation, apoptosis in CNS post-traumatic injury. In this review, we summarize the expression and functions of circRNAs in CNS in recent studies, as well as the circRNA-miRNA-mRNA interaction networks. The potential clinical value of circRNAs as therapeutic targets is also discussed.